Preparation method of wear-resistant and low-dielectric-constant PTFE composite material
By adding hollow glass microspheres and silicon nitride to the PTFE matrix and using supercritical CO2 assisted extrusion technology, the problem of difficult adjustment of PTFE dielectric constant and complex preparation method in the prior art is solved, and low dielectric constant is achieved and PTFE composite materials with high comprehensive performance are suitable for high-frequency electronic devices and high-speed data transmission and other fields.
Patent Information
- Application Number
- CN202510053409.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While reducing the dielectric constant of PTFE, the prior art is difficult to maintain its excellent comprehensive performance, and the preparation method is complex and is not suitable for large-scale production.
By adding hollow glass microspheres and silicon nitride to the PTFE matrix, and using supercritical CO2-assisted twin screw melt extrusion technology, uniform dispersion of fillers is achieved, dielectric constant is reduced, and mechanical properties and wear resistance are improved.
The prepared PTFE composite material has low dielectric constant, high thermal conductivity, high wear resistance and high overall strength, and is suitable for high-frequency electronic devices and high-speed data transmission fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a wear-resistant PTFE composite material with a low dielectric constant. Background Art
[0002] Polytetrafluoroethylene (PTFE) has extremely excellent dielectric properties, and its dielectric constant and dielectric loss are at the lowest values among many polymer materials (ε: 2.1, tan<0.0001). In addition, the bond energy of the CF bond is very high, it has good heat resistance, and has high thermal stability. At the same time, it has good chemical stability, low water absorption, good resistance to chemical corrosion, and small changes in dielectric properties within the high-frequency range. It is an ideal material for the application requirements of 5G high-frequency and high-speed substrate materials. However, PTFE also has its own shortcomings. Its chemical inertness makes it difficult to compound with other substances, and the adjustability of the dielectric constant is relatively poor. Therefore, it is necessary to modify the PTFE polymer to meet the performance requirements of high-frequency and high-speed substrate materials.
[0003] The existing solution is to change the dielectric constant of PTFE by adding fillers. Some researchers have tried to reduce the dielectric constant of PTFE by adding metal oxides, ceramic particles or carbon-based materials. However, these methods often lead to a decrease in other properties of PTFE (such as mechanical strength), or poor uniform dispersion of additives, thus affecting the overall performance of the composite material.
[0004] Although existing solutions can reduce the dielectric constant of PTFE to a certain extent, there are still some problems and limitations. First, if the added filler is improperly selected, it may react chemically or be physically incompatible with the PTFE matrix, thereby affecting the stability and long-term performance of the composite material. Secondly, even if the filler is properly selected, how to achieve uniform dispersion of the filler in the PTFE matrix is still a technical problem. If the filler is unevenly dispersed, it will cause the formation of conductive paths or dielectric discontinuous areas inside the composite material, thereby affecting the dielectric properties and mechanical properties of the composite material. In addition, the existing preparation method is usually cumbersome steps and complex equipment, which is not conducive to large-scale production and application. Therefore, how to maintain its excellent comprehensive performance while reducing the dielectric constant of PTFE, and to achieve the simplicity and feasibility of the preparation method, is the main challenge facing the current technology. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a wear-resistant, low dielectric constant PTFE composite material. The hollow glass microspheres and silicon nitride in the prepared PTFE composite material have a good matching effect, so that the obtained PTFE composite material has a low dielectric constant, high thermal conductivity, high wear resistance, and high overall strength.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a wear-resistant, low dielectric constant PTFE composite material comprises the following steps: S1: uniformly mixing the dried PTFE powder, filler and antioxidant to obtain a mixture; the filler is composed of at least one of hollow glass microspheres and modified hollow glass microspheres and at least one of silicon nitride and modified silicon nitride; S2: placing the mixed material into a twin-screw extruder for mixing, melt extrusion, introducing supercritical CO2 as an auxiliary extrusion medium during the extrusion process; and forming the melt-extruded composite material through a mold to obtain a composite material product; S3: performing annealing treatment on the composite material product.
[0007] In the PTFE composite material of the present invention, the hollow glass microspheres have a low density and can reduce the dielectric constant of the composite material system, and at the same time have excellent high temperature resistance and mechanical properties, including mechanical strength, modulus, wear resistance, etc. Silicon nitride (Si3N4) has excellent physical and chemical stability, which enables it to maintain stable performance in harsh environments such as high temperature and high humidity. When silicon nitride is added to the PTFE composite material as a filler, this stability helps the composite material to be used in a wider range of application fields, maintain a low dielectric constant, and effectively improve the hardness and wear resistance of the composite material.
[0008] Silicon nitride and hollow glass microspheres (HGM) play a synergistic role in PTFE composites. The combination of these two fillers can improve the mechanical properties and wear resistance of the composite while maintaining a low dielectric constant.
[0009] On this basis, the use of modified hollow glass microspheres and modified silicon nitride can make the hollow glass microspheres and silicon nitride more evenly dispersed in the PTFE matrix, and enhance the compatibility with the PTFE matrix, which can further reduce the dielectric constant of the PTFE composite material. In addition, the PTFE composite material can exhibit stronger wear resistance and excellent thermal conductivity.
[0010] In the above preparation method of the present invention, a high-speed mixer or a jet mill can be used for mixing to ensure uniform distribution of the filler in the matrix. Supercritical CO2 is introduced as an auxiliary extrusion medium during the extrusion process to promote the dispersion of the filler and the plasticization of the matrix by utilizing its good dissolution and diffusion properties. In addition, the PTFE powder, hollow glass microsphere raw material, and silicon nitride raw material are dried in advance to remove surface moisture and impurities to ensure stability during the melt extrusion process.
[0011] Preferably, the mixture comprises the following components in weight percentage: PTFE powder: 65-80 wt.%, hollow glass microspheres and / or modified hollow glass microspheres: 10-25 wt.%, silicon nitride and / or modified silicon nitride: 5-10 wt.%, antioxidant: 0.1-2.0 wt.%; the antioxidant is preferably 0.1-1.0 wt.%.
[0012] Preferably, the modified hollow glass microspheres include one or more of coupling agent modified hollow glass microspheres, coating modified hollow glass microspheres, plasma modified hollow glass microspheres, and laser modified hollow glass microspheres; The modified silicon nitride includes one or more of coupling agent modified silicon nitride, coating modified silicon nitride, plasma modified silicon nitride, and laser modified silicon nitride.
[0013] Preferably, the coupling agent used in the coupling agent-modified hollow glass microspheres and the coupling agent-modified silicon nitride is independently at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; Among them, when the hollow glass microspheres and silicon nitride are modified by coupling agents, the specific coupling agents can be: silane coupling agents: such as γ-aminopropyltriethoxysilane (KH550), whose main function is to enhance the interfacial bonding between the filler and the PTFE matrix through chemical bonding; titanate coupling agents: such as tetraisopropyl titanate (TPT), whose main function is to improve the dispersibility of the filler and its compatibility with the matrix; aluminate coupling agents: such as aluminate coupling agent A174, whose main function is to improve the surface properties of the filler and enhance the bonding with the matrix.
[0014] Preferably, the coatings in the coating-modified hollow glass microspheres and coating-modified silicon nitride are independently one of polymer coatings, metal oxide coatings, polymer / metal oxide composite coatings, and carbon-based coatings.
[0015] Preferably, the polymer in the polymer coating or polymer / metal oxide composite coating is polyvinyl alcohol; and the metal oxide in the metal oxide coating or polymer / metal oxide composite coating is nano-aluminum oxide.
[0016] Among them, when the polymer coating is a polyvinyl alcohol (PVA) coating, its main function is to enhance the interface bonding force between the filler and the PTFE matrix by forming a protective film; when the metal oxide coating is an aluminum oxide (Al2O3) coating, its main function is to improve the wear resistance and thermal stability of the filler and enhance the compatibility with the PTFE matrix; In addition, when the carbon-based coating is a graphene coating, its main function is to improve the overall performance of the composite material by providing excellent conductivity and mechanical strength.
[0017] The application of the surface coating of the present invention can significantly improve the compatibility of hollow glass microspheres and silicon nitride particles with the PTFE matrix, thereby improving the high temperature resistance, strength, wear resistance and low dielectric constant performance of the composite material.
[0018] Preferably, the preparation method of the coupling agent modified hollow glass microspheres or coupling agent modified silicon nitride comprises the following steps: dissolving the coupling agent in an organic solvent to prepare a coupling agent solution; placing hollow glass or silicon nitride in the coupling agent solution and stirring or ultrasonically treating it; then filtering and drying to obtain coupling agent modified hollow glass microspheres or coupling agent modified silicon nitride.
[0019] Preferably, the preparation method of the coating-modified hollow microspheres or coating-modified silicon nitride comprises the following steps: placing hollow glass microspheres or silicon nitride in a mixed solution containing coating materials, stirring or ultrasonically treating; then filtering and drying to obtain coating-modified hollow microspheres or coating-modified silicon nitride.
[0020] Preferably, the average particle size of the hollow glass microspheres is 1-50 µm; and the average particle size of the silicon nitride is 1-10 µm.
[0021] Preferably, in step S1, the antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant, and a thioether antioxidant. The hindered phenol antioxidant may be 2, 6-di-tert-butyl-4-methylphenol (BHT), which mainly functions to capture free radicals and prevent thermal oxidative degradation of the polymer; the phosphite antioxidant may be tris (2, 4-di-tert-butylphenyl) phosphite (Irgafos168); and the thioether antioxidant may be dilauryl sulfide (DLTDP), which mainly functions to react with free radicals, terminate free radical chain reactions, and delay thermal oxidative degradation of the polymer.
[0022] Preferably, in step S2, the pressure of supercritical CO2 is 12-25 MPa and the temperature is 40-120°C; In step S3, the annealing temperature is 100-130° C., and the annealing time is 10-60 min.
[0023] The beneficial effects of the present invention are: 1. The present invention solves the problem that traditional PTFE materials are limited in high-frequency electronic applications due to their high dielectric constant. By adding hollow glass microspheres and / or modified hollow glass microspheres, modified silicon nitride and / or modified silicon nitride to the PTFE matrix, and using supercritical CO2-assisted twin-screw melt extrusion technology, the uniform dispersion of each filler in the composite material has a significant impact on the dielectric constant, wear resistance, strength, etc. of the prepared PTFE composite material. This impact not only helps to reduce the dielectric constant of the composite material, but also improves the overall performance and application range of the composite material. The PTFE composite material prepared by the present invention has broad application prospects in the fields of high-frequency electronic devices, microwave communications, high-speed data transmission, etc. In these fields, materials with low dielectric constants can reduce energy loss and interference in the signal transmission process and improve the overall performance of the equipment.
[0024] The preparation method of the present invention adopts supercritical CO2-assisted twin-screw melt extrusion technology, which has the characteristics of simple equipment, convenient operation, and high production efficiency, and is conducive to large-scale production and application.
[0025] 2. The present invention uses hollow glass microspheres and silicon nitride as fillers, which solves the problem that if the fillers added in the prior art are improperly selected, they may react chemically or be physically incompatible with the PTFE matrix, thereby affecting the stability and long-term performance of the composite material. And by modifying the hollow glass microspheres and silicon nitride, the technical problem of uniform dispersion of hollow glass microspheres and silicon nitride in the PTFE matrix is further solved, and the uniform dispersion of hollow glass microspheres and silicon nitride in the PTFE matrix is achieved, avoiding the conductance path or dielectric discontinuous area caused by uneven dispersion of the filler, thereby ensuring the dielectric properties of the composite material. The present invention ensures the compatibility and stability of the filler with the PTFE matrix by combining the low density and low dielectric properties of the hollow glass microspheres and the high hardness and low dielectric constant advantages of silicon nitride. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In order to solve the problems in the prior art, the present invention provides a method for preparing a wear-resistant, low dielectric constant PTFE composite material, comprising the following steps: S1: uniformly mixing the dried PTFE powder, filler and antioxidant to obtain a mixture; the filler is composed of at least one of hollow glass microspheres and modified hollow glass microspheres and at least one of silicon nitride and modified silicon nitride; S2: putting the mixed material into a twin-screw extruder for mixing and melt extrusion, introducing supercritical CO2 as an auxiliary extrusion medium during the extrusion process; and forming the melt-extruded composite material through a mold to obtain a composite material product; S3: performing annealing treatment on the composite material product.
[0028] In some embodiments, the mixture includes the following components in weight percentage: PTFE powder: 65-80 wt.%, hollow glass microspheres and / or modified hollow glass microspheres: 10-25 wt.%, silicon nitride and / or modified silicon nitride: 5-10 wt.%, antioxidant: 0.1-2.0 wt.%.
[0029] In some embodiments, the modified hollow glass microspheres include one or more of coupling agent-modified hollow glass microspheres, coating-modified hollow glass microspheres, plasma-modified hollow glass microspheres, and laser-modified hollow glass microspheres; The modified silicon nitride includes one or more of coupling agent modified silicon nitride, coating modified silicon nitride, plasma modified silicon nitride, and laser modified silicon nitride.
[0030] In some embodiments, the coupling agent used in the coupling agent-modified hollow glass microspheres and the coupling agent-modified silicon nitride is independently at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; That is, the coupling agent modified hollow glass microspheres are one or more of silane coupling agent modified hollow glass microspheres, titanate coupling agent modified hollow glass microspheres, and aluminate coupling agent modified hollow glass microspheres; the coupling agent modified silicon nitride includes one or more of silane coupling agent modified silicon nitride, titanate coupling agent modified silicon nitride, and aluminate coupling agent modified silicon nitride; The silane coupling agent may specifically be γ-aminopropyltriethoxysilane (KH550), the titanate coupling agent may specifically be tetraisopropyl titanate (TPT), and the aluminate coupling agent may specifically be aluminate coupling agent A174.
[0031] In some embodiments, the coating in the coating-modified hollow glass microspheres and the coating-modified silicon nitride is independently one of a polymer coating, a metal oxide coating, a polymer / metal oxide composite coating, and a carbon-based coating.
[0032] Specifically, the coating-modified hollow glass microspheres include hollow glass microspheres and a coating coated on the surface of the hollow glass microspheres; the coating-modified hollow glass microspheres include one or more of polymer coating-modified hollow glass microspheres, metal oxide coating-modified hollow glass microspheres, polymer / metal oxide composite coating-modified hollow glass microspheres, and carbon-based coating-modified hollow glass microspheres.
[0033] The coating-modified silicon nitride includes silicon nitride and a coating applied on the surface of silicon nitride; the coating-modified silicon nitride includes one or more of polymer coating-modified silicon nitride, metal oxide coating-modified silicon nitride, polymer / metal oxide composite coating-modified silicon nitride, and carbon-based coating-modified silicon nitride.
[0034] Among them, the polymer coating can be specifically a polyvinyl alcohol (PVA) coating, the metal oxide coating can be specifically an aluminum oxide (Al2O3) coating, the polymer / metal oxide composite coating can be specifically a polyvinyl alcohol / aluminum oxide composite coating, and the carbon-based coating can be specifically a graphene coating.
[0035] In some embodiments, the method for preparing coupling agent-modified hollow glass microspheres comprises the following steps: dissolving the coupling agent in an organic solvent to prepare a coupling agent solution; placing the hollow glass microspheres in the coupling agent solution and stirring or ultrasonically treating the solution; then filtering and drying the solution to obtain coupling agent-modified hollow glass microspheres; The preparation method of the coating-modified hollow microspheres comprises the following steps: placing the hollow glass microspheres in a mixed solution containing coating materials, stirring or ultrasonically treating the mixture so that the coating materials are coated on the particle surfaces; and then filtering and drying to obtain the coating-modified hollow microspheres.
[0036] In some embodiments, the preparation method of coupling agent modified silicon nitride comprises the following steps: dissolving the coupling agent in an organic solvent to prepare a coupling agent solution; placing silicon nitride in the coupling agent solution and stirring or ultrasonically treating it; then filtering and drying to obtain coupling agent modified silicon nitride; The preparation method of the coating-modified silicon nitride comprises the following steps: placing hollow glass microspheres in a mixed solution containing a coating material, stirring or ultrasonically treating the mixture so that the coating material is coated on the surface of the silicon nitride; and then filtering and drying to obtain the coating-modified silicon nitride.
[0037] In some preferred embodiments, the coupling agent-modified hollow glass microspheres are hollow glass microspheres modified by silane coupling agents, the coupling agent-modified silicon nitride is silicon nitride modified by silane coupling agents, and the silane coupling agent is γ-aminopropyltriethoxysilane (KH550).
[0038] The specific preparation method of the silane coupling agent modified hollow glass microspheres comprises the following steps: Dissolving γ-aminopropyltriethoxysilane in ethanol to prepare a 1.5-3.5 wt.% γ-aminopropyltriethoxysilane solution; placing hollow glass microspheres in the γ-aminopropyltriethoxysilane solution with a mass of 10-15 times the mass of the hollow glass microspheres, stirring for 1-2 h; then filtering, and vacuum drying at 50-60 °C to obtain γ-aminopropyltriethoxysilane-modified hollow glass microspheres; The specific preparation method of silane coupling agent modified silicon nitride comprises the following steps: dissolving γ-aminopropyltriethoxysilane in ethanol to obtain 0.8-2.0 wt.% γ-aminopropyltriethoxysilane solution; placing silicon nitride in 15-20 times the mass of the γ-aminopropyltriethoxysilane solution and stirring for 1.5-3 h; then filtering and vacuum drying at 50-60 ° C to obtain γ-aminopropyltriethoxysilane modified silicon nitride.
[0039] In some preferred embodiments, the coating-modified hollow glass microspheres are hollow glass microspheres modified by alumina coatings or hollow glass microspheres modified by polyvinyl alcohol / alumina composite coatings; The method for preparing hollow glass microspheres modified by alumina coating comprises the following steps: The hollow glass microspheres are added to a nano-alumina aqueous dispersion 10-15 times their mass, stirred for 3-6 hours, then filtered and vacuum dried at 50-60 °C to obtain hollow glass microspheres modified with an alumina coating. The concentration of nano-alumina in the nano-alumina aqueous dispersion is 10-25 mg / mL; The method for preparing polyvinyl alcohol / alumina composite coating modified hollow glass microspheres comprises the following steps: Polyvinyl alcohol and nano-alumina aqueous dispersion are used to prepare polyvinyl alcohol / nano-alumina aqueous dispersion; in the polyvinyl alcohol / nano-alumina aqueous dispersion, the concentration of polyvinyl alcohol is 3-8 mg / mL; the concentration of nano-alumina is 10-25 mg / mL; The hollow glass microspheres are added into a polyvinyl alcohol / nano-alumina aqueous dispersion with a mass 10-15 times that of the hollow glass microspheres, and stirred for 3-6 hours; then filtered and vacuum dried at 50-60°C to obtain polyvinyl alcohol / alumina composite coating modified hollow glass microspheres.
[0040] In some preferred embodiments, the coating-modified silicon nitride is an aluminum oxide coating-modified silicon nitride or a polyvinyl alcohol / aluminum oxide composite coating-modified silicon nitride; The preparation method of aluminum oxide coating modified silicon nitride comprises the following steps: Add silicon nitride to a nano-alumina aqueous dispersion 20-25 times its mass, stir for 4-8 hours, filter, and vacuum dry at 50-60 °C to obtain alumina-coated modified silicon nitride. The concentration of nano-alumina in the nano-alumina aqueous dispersion is 10-25 mg / mL; The preparation method of polyvinyl alcohol / aluminum oxide composite coating modified silicon nitride comprises the following steps: Polyvinyl alcohol and nano-alumina aqueous dispersion are used to prepare polyvinyl alcohol / nano-alumina aqueous dispersion; in the polyvinyl alcohol / nano-alumina aqueous dispersion, the concentration of polyvinyl alcohol is 3-8 mg / mL; the concentration of nano-alumina is 10-25 mg / mL; Silicon nitride is added to a polyvinyl alcohol / nano-alumina aqueous dispersion with a mass 20-25 times that of silicon nitride, and stirred for 3-6 hours; then filtered and vacuum dried at 60°C to obtain polyvinyl alcohol / alumina composite coating modified silicon nitride.
[0041] In the above preparation method, the preparation method of the nano-alumina aqueous dispersion involved includes the following steps: adding nano-alumina, ethylene glycol monoethyl ether, sodium carboxymethyl cellulose, and γ-aminopropyl triethoxysilane to water, stirring and mixing while ultrasonically dispersing for 1-3 hours to obtain a nano-alumina aqueous dispersion. The particle size of the nano-alumina is 5-30 nm; the mass ratio of the added nano-alumina, ethylene glycol monoethyl ether, sodium carboxymethyl cellulose, and γ-aminopropyl triethoxysilane is 1:2-4:0.1-0.3:0.01-0.1.
[0042] In some embodiments, the average particle size of the hollow glass microspheres is 1-50 µm; and the average particle size of the silicon nitride is 1-10 µm.
[0043] In some embodiments, in step S1, the antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant, and a thioether antioxidant. The hindered phenol antioxidant may be 2,6-di-tert-butyl-4-methylphenol (BHT), the phosphite antioxidant may be tris(2,4-di-tert-butylphenyl)phosphite (Irgafos168), and the thioether antioxidant may be dilauryl sulfide (DLTDP).
[0044] In some embodiments, in step S2, the pressure of supercritical CO2 is 12-25 MPa and the temperature is 40-120°C; wherein, the supercritical auxiliary extrusion equipment used for introducing supercritical CO2 as an auxiliary extrusion medium during the extrusion process can refer to the literature (Research on Supercritical CO2 Assisted PTFE / PP Extrusion, Engineering Plastics Application, 2008, 36 (2): 35-37.); In step S3, the annealing temperature is 100-130° C., and the annealing time is 10-60 min.
[0045] The following are specific examples and comparative examples. The hollow glass microspheres (HGM) and silicon nitride used in the following examples have an average diameter of 50 µm, a density of 0.1 g / cm³, and a dielectric constant of 1.2 for HGM; an average particle size of 1 µm, a density of 3.2 g / cm³, and a dielectric constant of 3.5 for silicon nitride.
[0046] Embodiment 1: A method for preparing a wear-resistant, low dielectric constant PTFE composite material comprises the following steps: S1: drying PTFE powder, hollow glass microspheres, and silicon nitride, and then mixing the dried PTFE powder, hollow glass microspheres, silicon nitride, and 2,6-di-tert-butyl-4-methylphenol uniformly with a high-speed mixer to obtain a mixture; The mixture includes the following components in weight percentage: PTFE powder: 74.5 wt.%, hollow glass microspheres: 15.0 wt.%, silicon nitride: 10.0 wt.%, 2, 6-di-tert-butyl-4-methylphenol: 0.5 wt.%; S2: putting the mixed material into a twin-screw extruder for mixing and melt extrusion, introducing supercritical CO2 as an auxiliary extrusion medium during the extrusion process, the supercritical CO2 pressure is 20 MPa, and the temperature is 80°C; and forming the melt-extruded composite material through a mold to obtain a composite material product; The temperature of the twin-screw extruder was set as follows: 290 °C in zone 1, 330 °C in zone 2, 345 °C in zone 3, 365 °C in zone 4, and 370 °C in zone 5, and the screw speed was 100 rpm.
[0047] S3: annealing the composite material product; the annealing temperature is 120°C, and the annealing time is 50 min.
[0048] Embodiment 2: A method for preparing a wear-resistant, low dielectric constant PTFE composite material, which is different from Example 1 in that hollow glass microspheres and silicon nitride are replaced by silane coupling agent-modified hollow glass microspheres and silane coupling agent-modified silicon nitride, respectively; The preparation method of hollow glass microspheres modified by silane coupling agent comprises the following steps: γ-aminopropyltriethoxysilane was dissolved in ethanol to prepare a 2.0 wt.% γ-aminopropyltriethoxysilane solution; hollow glass microspheres were placed in the γ-aminopropyltriethoxysilane solution with a mass 12 times that of the hollow glass microspheres and stirred for 1.5 h; the hollow glass microspheres were then filtered and vacuum dried at 60 °C to obtain γ-aminopropyltriethoxysilane-modified hollow glass microspheres; The specific preparation method of silane coupling agent modified silicon nitride comprises the following steps: γ-aminopropyltriethoxysilane was dissolved in ethanol to prepare a 1.0 wt.% γ-aminopropyltriethoxysilane solution; silicon nitride was placed in the γ-aminopropyltriethoxysilane solution with a mass 18 times that of the γ-aminopropyltriethoxysilane solution and stirred for 2 h; then the solution was filtered and vacuum dried at 60 °C to obtain γ-aminopropyltriethoxysilane-modified silicon nitride.
[0049] Embodiment 3: A method for preparing a wear-resistant, low dielectric constant PTFE composite material, which is different from Example 1 in that hollow glass microspheres and silicon nitride are replaced by hollow glass microspheres modified by aluminum oxide coatings and silicon nitride modified by aluminum oxide coatings, respectively; The method for preparing hollow glass microspheres modified by alumina coating comprises the following steps: The hollow glass microspheres were added to a nano-alumina aqueous dispersion with a mass 10 times that of the hollow glass microspheres and stirred for 4 h. The hollow glass microspheres were then filtered and vacuum dried at 60 °C to obtain hollow glass microspheres modified with an alumina coating. The concentration of nano-alumina in the nano-alumina aqueous dispersion was 20 mg / mL.
[0050] The preparation method of aluminum oxide coating modified silicon nitride comprises the following steps: Silicon nitride was added to a nano-alumina aqueous dispersion with a mass 20 times that of silicon nitride, stirred for 5 h, filtered, and vacuum dried at 60 °C to obtain silicon nitride modified with an alumina coating. The concentration of nano-alumina in the nano-alumina aqueous dispersion was 20 mg / mL.
[0051] The preparation method of nano-alumina aqueous dispersion comprises the following steps: adding nano-alumina, ethylene glycol monoethyl ether, sodium carboxymethyl cellulose, and γ-aminopropyl triethoxysilane to water, stirring and mixing while ultrasonically dispersing for 1 hour to obtain nano-alumina aqueous dispersion. The particle size of the nano-alumina is 5-30 nm; the mass ratio of the added nano-alumina, ethylene glycol monoethyl ether, sodium carboxymethyl cellulose, and γ-aminopropyl triethoxysilane is 1:3:0.15:0.05.
[0052] Embodiment 4: A method for preparing a wear-resistant, low dielectric constant PTFE composite material, which is different from Example 1 in that hollow glass microspheres and silicon nitride are replaced by hollow glass microspheres modified by polyvinyl alcohol / alumina composite coatings and silicon nitride modified by polyvinyl alcohol / alumina composite coatings, respectively; The method for preparing polyvinyl alcohol / alumina composite coating modified hollow glass microspheres comprises the following steps: Polyvinyl alcohol and nano-alumina aqueous dispersion are used to prepare polyvinyl alcohol / nano-alumina aqueous dispersion; in the polyvinyl alcohol / nano-alumina aqueous dispersion, the concentration of polyvinyl alcohol is 5 mg / mL; the concentration of nano-alumina is 20 mg / mL; The hollow glass microspheres were added into a polyvinyl alcohol / nano-alumina aqueous dispersion with a mass 10 times that of the hollow glass microspheres and stirred for 4 hours. The mixture was then filtered and vacuum dried at 60°C to obtain the polyvinyl alcohol / alumina composite coating-modified hollow glass microspheres.
[0053] The preparation method of polyvinyl alcohol / aluminum oxide composite coating modified silicon nitride comprises the following steps: Polyvinyl alcohol and nano-alumina aqueous dispersion are used to prepare polyvinyl alcohol / nano-alumina aqueous dispersion; in the polyvinyl alcohol / nano-alumina aqueous dispersion, the concentration of polyvinyl alcohol is 5 mg / mL; the concentration of nano-alumina is 20 mg / mL; Silicon nitride was added into a polyvinyl alcohol / nano-alumina aqueous dispersion with a mass 20 times that of silicon nitride and stirred for 4 h. The dispersion was then filtered and dried in vacuum at 60 °C to obtain polyvinyl alcohol / alumina composite coating modified silicon nitride.
[0054] The preparation method of nano-alumina aqueous dispersion comprises the following steps: adding nano-alumina, ethylene glycol monoethyl ether, sodium carboxymethyl cellulose, and γ-aminopropyl triethoxysilane to water, stirring and mixing while ultrasonically dispersing for 1 hour to obtain nano-alumina aqueous dispersion. The particle size of the nano-alumina is 5-30 nm; the mass ratio of the added nano-alumina, ethylene glycol monoethyl ether, sodium carboxymethyl cellulose, and γ-aminopropyl triethoxysilane is 1:3:0.15:0.05.
[0055] Embodiment 5: A method for preparing a wear-resistant, low dielectric constant PTFE composite material. Different from Example 4, the mixture includes the following components in weight percentage: PTFE powder: 65.9 wt.%, polyvinyl alcohol / alumina composite coating modified hollow glass microspheres: 25.0 wt.%, polyvinyl alcohol / alumina composite coating modified silicon nitride: 9 wt.%, 2, 6-di-tert-butyl-4-methylphenol: 0.1 wt.%.
[0056] Embodiment 6: A method for preparing a wear-resistant, low dielectric constant PTFE composite material. Different from Example 4, the mixture includes the following components in weight percentage: PTFE powder: 80.0 wt.%, polyvinyl alcohol / aluminum oxide composite coating modified hollow glass microspheres: 10.0 wt.%, polyvinyl alcohol / aluminum oxide composite coating modified silicon nitride: 9.5 wt.%, 2, 6-di-tert-butyl-4-methylphenol: 0.5 wt.%.
[0057] Embodiment 7: A method for preparing a wear-resistant, low dielectric constant PTFE composite material. Different from Example 4, the mixture includes the following components in weight percentage: PTFE powder: 69.5 wt.%, polyvinyl alcohol / alumina composite coating modified hollow glass microspheres: 25.0 wt.%, polyvinyl alcohol / alumina composite coating modified silicon nitride: 5.0 wt.%, 2,6-di-tert-butyl-4-methylphenol: 0.5 wt.%.
[0058] The PTFE composite material prepared in the embodiment was subjected to performance tests, including tensile strength, wear resistance, dielectric constant and thermal conductivity. The mechanical strength test was performed using a universal material testing machine, and the test conditions were room temperature and loading speed: 1 mm / min. The wear resistance of the composite material was tested using a wear tester, and the test conditions were: load 10 N, sliding speed 200 rpm, and test time 30 min. The specific test results are shown in Table 1:
[0059] Table 1 Performance test results of PTFE composite materials
[0060] As can be seen from Table 1, the PTFE composite material prepared by the method of the present invention has a low dielectric constant, a small friction coefficient, and high thermal conductivity and tensile strength. As can be seen from the comparison of Examples 1-4, for hollow glass microspheres and silicon nitride, in terms of technical effects, the filler modified by the polyvinyl alcohol / alumina composite coating>the filler modified by the alumina coating>the filler modified by the silane coupling agent>the unmodified filler.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a wear-resistant, low dielectric constant PTFE composite material, characterized in that: The following steps are involved: S1: uniformly mixing the dried PTFE powder, filler and antioxidant to obtain a mixture; the filler is composed of at least one of hollow glass microspheres and modified hollow glass microspheres and at least one of silicon nitride and modified silicon nitride; S2: placing the mixed material into a twin-screw extruder for mixing, melt extrusion, introducing supercritical CO2 as an auxiliary extrusion medium during the extrusion process; and forming the melt-extruded composite material through a mold to obtain a composite material product; S3: performing annealing treatment on the composite material product.
2. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to claim 1, characterized in that: The mixture comprises the following components in weight percentage: PTFE powder: 65-80 wt.%, hollow glass microspheres and / or modified hollow glass microspheres: 10-25 wt.%, silicon nitride and / or modified silicon nitride: 5-10 wt.%, antioxidant: 0.1-2.0 wt.%.
3. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to claim 1, characterized in that: The modified hollow glass microspheres include one or more of coupling agent modified hollow glass microspheres, coating modified hollow glass microspheres, plasma modified hollow glass microspheres, and laser modified hollow glass microspheres; The modified silicon nitride includes one or more of coupling agent modified silicon nitride, coating modified silicon nitride, plasma modified silicon nitride, and laser modified silicon nitride.
4. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to claim 3, characterized in that: The coupling agent used in the coupling agent-modified hollow glass microspheres and the coupling agent-modified silicon nitride is independently at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; The coatings in the coating-modified hollow glass microspheres and coating-modified silicon nitride are independently one of polymer coatings, metal oxide coatings, polymer / metal oxide composite coatings, and carbon-based coatings.
5. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to claim 4, characterized in that: The polymer in the polymer coating and the polymer / metal oxide composite coating is polyvinyl alcohol; the metal oxide in the metal oxide coating and the polymer / metal oxide composite coating is nano-aluminum oxide.
6. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to claim 3, characterized in that: The preparation method of the coupling agent modified hollow glass microsphere or coupling agent modified silicon nitride comprises the following steps: dissolving the coupling agent in an organic solvent to prepare a coupling agent solution; placing hollow glass or silicon nitride in the coupling agent solution and stirring or ultrasonically treating it; and then filtering and drying to obtain the coupling agent modified hollow glass microsphere or coupling agent modified silicon nitride.
7. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to claim 3, characterized in that: The preparation method of the coating-modified hollow microspheres or coating-modified silicon nitride comprises the following steps: placing hollow glass microspheres or silicon nitride in a mixed solution containing coating materials, stirring or ultrasonically treating; and then filtering and drying to obtain coating-modified hollow microspheres or coating-modified silicon nitride.
8. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to any one of claims 1 to 7, characterized in that: The average particle size of the hollow glass microspheres is 1-50 μm; the average particle size of the silicon nitride is 1-10 μm.
9. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to any one of claims 1 to 7, characterized in that: In step S1, the antioxidant includes one or more of hindered phenol antioxidants, phosphite antioxidants, and thioether antioxidants.
10. The method for preparing the wear-resistant, low dielectric constant PTFE composite material according to any one of claims 1 to 7, characterized in that: In step S2, the pressure of supercritical CO2 is 12-25 MPa and the temperature is 40-120°C; In step S3, the annealing temperature is 100-130° C., and the annealing time is 10-60 min.
Citation Information
Patent Citations
Extrusion grade fluorin plastic composition processed with supercritical CO2 assistance
CN103113696A
Low dielectric constant fluorine-containing polymer composite material and preparation method thereof
CN107674349A
Fluorine-containing resin composition, resin glue solution containing fluorine-containing resin composition, fluorine-containing dielectric sheet, laminated board, copper-clad board and printed circuit board
CN112574521A
PTFE-hollow glass microsphere composite material as well as preparation method and application thereof
CN114516993A
Resin composition and application thereof
CN118852815A